12th IEEE Real-Time and Embedded Technology and Applications Symposium (RTAS'06)
DOI: 10.1109/rtas.2006.35
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Scheduling on Multicore Platforms

Abstract: Multicore architectures, which have multiple processing units on a single chip, are widely viewed as a way to achieve higher processor performance, given that thermal and power problems impose limits on the performance of single-core designs. Accordingly, several chip manufacturers have already released, or will soon release, chips with dual cores, and it is predicted that chips with up to 32 cores will be available within a decade. To effectively use the available processing resources on multicore platforms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 21 publications
1
63
0
1
Order By: Relevance
“…They showed that L2 contention can be reduced, and throughput improved, by discouraging threads that generate significant memory-to-L2 traffic from being co-scheduled. In recent work [1], we presented results comparable to those of Fedorova et al but pertaining to real-time systems. Specifically, we showed that it is possible to discourage high- * Work supported by a grant from Intel Corp. and by NSF grants CNS 0309825, CNS 0408996, and CCF 0541056.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…They showed that L2 contention can be reduced, and throughput improved, by discouraging threads that generate significant memory-to-L2 traffic from being co-scheduled. In recent work [1], we presented results comparable to those of Fedorova et al but pertaining to real-time systems. Specifically, we showed that it is possible to discourage high- * Work supported by a grant from Intel Corp. and by NSF grants CNS 0309825, CNS 0408996, and CCF 0541056.…”
Section: Introductionsupporting
confidence: 80%
“…There are several directions for future work. First, we want to combine this scheduling method with the methods in [1] so that both the "encouragement" and "discouragement" of co-scheduling can be supported in the same system. Second, we wish to include support for critical sections and precedence constraints in our work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-core platform provides an environment to accomplish computation-intensive and complicated arithmetic real-time parallel issues. Multiprocessors proved that increasing the core count on a single die is the better solution than increasing processor clock frequencies (Where this idea suffers with power leakage issue [17], [14], [9]). Numerous single core issues need to be addressed and new approaches need to be advocated and evaluated on multi-core systems [15].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-core computing platforms can further aggravate the complexity of WCET analysis due to the possible inter-thread interferences in shared resources such as L2 caches, which are very difficult to analyze statically. While there have been recent studies on real-time scheduling for multi-core platforms Anderson et al 2006], all these studies basically assume that the worst-case performance of real-time threads is known. Therefore, it is a necessity to reasonably bound the WCET of real-time threads running on multi-core processors before the multi-core platforms can be safely employed by real-time systems.…”
Section: Introductionmentioning
confidence: 99%